Legal Innovation and AI Integration in the Management of Community Development and Empowerment Obligations by Coal Mining Companies - Badrunsyah; Mugiati (Jurnal Greenation Sosial dan Politik, 2025)
Coal mining companies in Indonesia are required to implement the Community Development and Empowerment (PPM) program as a form of social responsibility and contribution to local development. However, the implementation of this program is still faced with a number of obstacles such as weak supervision, lack of community participation, and limited transparency. This research aims to examine how legal innovation and artificial intelligence (AI) integration can improve the governance of PPM obligations in a more efficient, accountable, and sustainable manner. This research is a qualitative normative juridical study, which examines legal norms with a descriptive-analytical approach, to understand how the law should apply in the context of the implementation of Community Development and Empowerment (PPM) obligations by coal mining companies and how the integration of technology, especially artificial intelligence (AI), can be accommodated in the legal system. The results of the study revealed that the use of AI technology, such as data analysis, digital reporting systems, and community feedback platforms, is able to increase the effectiveness and transparency of the implementation of the PPM program. On the other hand, legal innovation is needed in the form of regulatory reforms that support technology-based systems and active community involvement. This study concludes that the integration of legal innovation and AI technology can be a strategic solution in strengthening the implementation of PPM obligations by coal mining companies, while encouraging the realization of social justice and sustainable development in mining areas.